Competency model at Primary Teaching degree of the Faculty of Education of the University of Zaragoza: a preliminary study (Revista educación, investigación, innovación y transferencia, 2021)
This study analyses how transversal skills are developed and evaluated in the Primary Education Teaching degree at the University of Zaragoza. To this aim, 26 members of various groups of the educational community were surveyed, including university students, professors, active and retired teachers. Proposals about competence process in the Faculty and implementing the changes associated with convergence towards the EHEA under the most appropriate conditions have been showed. The opinions were associated collected through discussion groups that were analysed afterwards using the software NVIVO11. The most relevant results show the importance of establishing a competences-based education model in the Education Faculty, in order to evaluate it and its impact on the students formation. A constant critical reflection by teachers about their teaching practice and consider evaluation as an instrument to learn and discover learning, are two other needs that arise in this work. In addition, to move towards a culture of collaboration and greater teacher training, where competences acquire the importance and priority they deserve. Emotional intelligence and “learn how to learn” appear as more relevant proposals. The results obtained in this project provide a tool that allows the Faculty to improve and advance toward integral training models for the teachers of the future.